Effectiveness of respiratory proprioceptive neuromuscular facilitation technique on pulmonary function in spinal cord injury patients: a randomized controlled trial - Thorat, Komal D.; Tungikar, Sudhir; Lofvenmark, Inka (International Journal of Research in Medical Sciences, 2024)
Background: Spinal cord injury (SCI) often leads to respiratory complications due to impaired neuromuscular control. Proprioceptive neuromuscular facilitation (PNF) techniques have shown promise in improving respiratory function in various populations, but their effectiveness in SCI patients remains underexplored. This study aimed to investigate the effectiveness of respiratory PNF techniques on pulmonary function in individuals with SCI. Methods: A randomized controlled trial was conducted involving SCI patients with respiratory impairment. A total of 43 participants were included in this study. The study duration was 4 years with an intervention period of 4 weeks and the outcome measures were pulmonary functions and chest expansion using inch tape. Results: There was a significant improvement in pulmonary functions in the control group and a highly significant improvement in pulmonary functions in the experimental group after 4 weeks of interventions and chest expansion was significantly improved in the experimental group. Conclusions: The respiratory PNF techniques demonstrated a clinically meaningful enhancement in pulmonary function and chest mobility among SCI patients. Respiratory PNF techniques represent a valuable adjunct therapy for improving pulmonary function and chest mobility in individuals with SCI.